The digital mom handbook : how to blog, vlog, tweet, and facebook your way to a dream career at home - McClelland, Audrey Couto. (Harper Business, 2011)
"Mothers have been looking for the middle ground for more than half a century. Staying at home and raising the kids full-time isn't it. Working full-time and rushing home to tuck the kids in at 7 p.m. sharp ain't it either. Even part-time work outside the house can be a scramble for most women, as they try to "have it all" between 9 am and 5 pm. To work or not to work? That seems to be the bottom-line question for most women today. But, Audrey McClelland and Colleen Padilla are proving that the equation is changing. Both of them left behind the corporate ladder and Ivy League degrees to stay home with their children; but, instead of assigning them permanent stay-at-home status, this choice was the catalyst to their reinvention. Miles apart, they each sat down at their computers one day and began to blog. Slowly but surely, their audiences grew. The portability of computers and smart-phones, the connective powers of social networks, and an overwhelming desire to happily mix work and family enabled them to move past the Mommy Wars (i.e. stay at home mom vs. working mom) into a territory all their own. Audrey and Colleen literally blogged, tweeted, skyped, vlogged, and facebooked their ways to the top. In THE DIGITAL MOM HANDBOOK they will show other moms how to find middle ground--via the frontier of the Internet--too. Do you want to be a booming six-figure eBay saleswoman? A 20-hour-a-week brand consultant? A local Twitter correspondent? The terms are yours to define. Money, hours-per-week, title--these don't dictate your Digital Mom success. Personal satisfaction does"--